The Effect of the Think Pair Share for Elementary School Students in Learning Changes in Matter - Halimatusy Sya’diyah; Petra Kristi Mulyani (Jurnal Penelitian Pendidikan IPA, 2025)
This research was a quantitative research conducted in a fourth grade elementary school. The study aimed to determine the effect of the Think Pair Share (TPS) learning model on students’ activeness and learning outcomes in fourth grade subject of changes in matter on the natural science subjects. Data collection techniques were observation and questionnaire. Data analysis in this study to finded the validity, reliability, hypothesis, and N-Gain Score tests. The hypothesis of was tested using t-test to find the influence of variables X1 to Y and X2 to Y. The results showed the t-test coefficient of the TPS learning model on learning outcomes obtained a significance value of 0.000 < 0.05, meaning that there is an influence of the TPS learning model on learning outcomes. N-Gain results was 61.40, the meaning that the application of the TPS learning model improved students learning outcomes in the category of moderately effective. The result of TPS learning model on students’ activeness obtained a value of 1972 in the very active category. It was showed the TPS learning model was very influential on increase student activeness.